Enhanced bioelectrochemical performance of microbial fuel cell with titanium dioxide-attached dual metal organic frameworks grown on zinc aluminum - layered double hydroxide as cathode catalyst. (May 2022) - Chen, Junfeng; Yang, Jiaqi; Wang, Xuemei; Yang, Daoxin; Wang, Xu; Zhang, Yuhui; Du, Yuru; Wang, Yongle; Wei, Qingying; Wang, Renjun; Liu, Yanyan; Yang, Yuewei
Graphical abstract: Highlights: TiO2 @ZIF-67/ZIF-8@ZnAl-LDH was successfully prepared by distributed feeding method. TiO2 @ZIF-67/ZIF-8@ZnAl-LDH was stable, conductivity and multiple reaction sites. Maximum power density of TiO2 @ZIF-67/ZIF-8@ZnAl-LDH-MFC was 409.6 mW/m 2. The combined action of LDH, dual MOFs and TiO2 enhanced the MFC performance. Abstract: In this study, a three-step distributed feeding method was used to prepare TiO2 -attached dual CoZn-metal organic frameworks growing on ZnAl-layered double hydroxide (TiO2 @ZIF-67/ZIF-8@ZnAl-LDH) as cathode catalyst of microbial fuel cell (MFC). The composite material was a composite core–shell structure constructed by multi-layer coating with sheet-like ZnAl-LDH as the base, dual MOFs as the magnetic core and TiO2 as the rough surface. The composite material had crystal planes (0 0 9), (1 1 0), (1 0 1) interface. The rough surface, core–shell core and polyhedral structure of TiO2 @ZIF-67/ZIF-8@ZnAl-LDH were observed. The complete distribution of Ti, Zn, Al, and Co in the material was observed and offered active sites. The contents of Ti (15.97 %), Al (5.53 %), Na (5.04 %), N (3.52%), Zn (1.47 %) were found out. TiO2 @ZIF-67/ZIF-8@ZnAl-LDH was excellent in electrochemical activity and the maximum power density was 409.6 mW/m 2, the stable continuous output voltage was 538.4 mV for 8 d.